REVIEW : OF SUPERDISINTEGRANT INGREDIENTS IN FAST DISINTEGRANT TABLET TABLET PREPARATIONS - Fahmansyah, Lingga Pratama; Agus S; Suparman (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
This study aimed to evaluate the potential of synthetic and natural disintegrating agents in fast-disintegrating tablet (FDT) formulations. The methodology used includes a comprehensive literature review on the definition, characteristics, working mechanisms, and applications of super disintegrants in the manufacture of FDTs. The results of the study showed that super disintegrants play an important role in facilitating rapid disintegration of tablets. Synthetic super disintegrants such as crospovidone, croscarmellose sodium, and sodium starch glycolate have the advantage of lower concentrations and better intragranular effectiveness. On the other hand, natural superdisintegrants such as mucilages, gums, and polysaccharides from plants have easy availability, affordable prices, non-toxic properties, and biologically acceptable characteristics. In conclusion, the selection of an appropriate super disintegrant, whether synthetic or natural, is a key factor in effective FDT formulation and providing rapid disintegration. The combination of using super disintegrants at the granulation stage (intragranular) and before compression (extragranular) can produce better performance compared to a single method.  Keywords: FDT, Super disintegrant, Synthetic, Natural